Asesment Bangunan Gedung di Universitas Tadulako Palu pasca Gempa 28 September 2018 untuk Pelaksanaan Rehabilitasi dan Rekonstruksi - Sulendra, I.K. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
After September 28 2018 Palu strong shock (7,5 Mw) caused damages of buildings, not exceptly on Tadulako University in Palu City. Those secondary impact of earthquakes i.e: lighweight, moderate, heavy damages until collaps of buildings. Therefore those impact caused activity proccess in this campus delayed. After shock caused damages many building, assessment of those buildings are necessary. Output of assessment needed for rehabilitation and reconstruction stages. The characteristics and types of damages very important to knew to next stages i.e: built back better post of earthquake disaster. Generally methods of assessment buildings after shock i.e : Rapid Visual Screening (RPS), Semi Destructive and Rapis Analysis and Detailing Analysis include Review Design with Up to Date Standard Design. This assessment used “Quick Assessment for Non Engineered Structures” from Directorat General of Building PUPR for simple building (only one story building) and Level-1 Assessment Methods from World Bank for Engineered Structures. Those assessment verification of : 140 unit building , 69 unit and 19 unit of lighweight, moderate ang heavy damages until failure respectively. Two years after the disaster, rehabilitation and reconstruction process i.e: 160 unit of non engineered building with lightweight-moderate damage has been repaired. Then on going process build of 10 muliperpuse steel frame of two stories building, with 12 class room each buildings. For engineered building with moderate damage category, this year until next year to retroffiting of structurals elemens, this retrofit to do for anticipate the next damage earthquakes. The rehabilitation and reconstruction process until 2023 for completly build after Palu Earthquakes. Next year until 2023 priority rehabilitation and rehabilitation for retroffiting main engineered structures building i.e: rektorat, auditorium, hospital, laboratory and rechange collaping building after diasaster.